Tubal surgery in female infertility - Jefferson Cortéz, Luz (2015)
This work was done in the service of the Archbishop Loayza Hospital Infertility. 45 cases of infertile women with tubal factor is presented. All patients with histersalpingografía counted. In the background prevailed abortion, pelvic inflammatory disease and pelvic surgery, 24% had no antecedent, 4 patients had genital TB. The surgical techniques used were, cornual reimplantation and salpingolisis, fimbriostomía and tubal anastomosis, 10 patients came to gestate, 2 of these pregnancies were ectopic pregnancies, one patient treated with genital TB had two normal pregnancies.